Effect of Zeolite Mesh Size Variation on the Filtration Performance of Zeolite-PAN/PVDF Nanofiber for Methylene Blue Dye Removal - Buya, Dheace Gracesela; Aflaha , Rizky; Rianjanu, Aditya (Greensusmater, 2025)
Water pollution from industrial effluents, particularly synthetic dyes like methylene blue (MB), poses significant environmental challenges. Electrospun nanofiber membranes based on polyacrylonitrile (PAN) and polyvinylidene fluoride (PVDF) are promising for filtration due to their high surface area and porous structure. However, their limited dye adsorption capacity requires enhancement, which can be achieved by incorporating natural zeolite particles known for their high ion-exchange capacity. In this study, we developed Ze-PAN/PVDF nanofiber membranes using zeolite with varying particle sizes (mesh sizes 50, 100, 200, 300) via vacuum filtration and evaluated their performance in MB dye removal. All Ze-PAN/PVDF membranes exhibited high initial dye rejection (above 97%) in the first two cycles, while the control PAN/PVDF membrane showed minimal rejection, decreasing from 35% to 7% over five cycles. The decline in rejection efficiency became noticeable from the third cycle, with values of 67%, 39%, 74%, and 86% for Ze50, Ze100, Ze200, and Ze300, respectively. Permeation flux was significantly affected by zeolite particle size, with the PAN/PVDF membrane maintaining a high flux (>10,000 L m⁻² h⁻¹ bar⁻¹), while Ze50-PAN/PVDF dropped to 260 ± 30 L m⁻² h⁻¹ bar⁻¹. Finer particles in Ze300-PAN/PVDF maintained relatively higher flux (370 ± 200 L m⁻² h⁻¹ bar⁻¹), indicating reduced pore blockage. These findings highlight the importance of optimizing zeolite particle size to achieve high dye removal efficiency and stable flux, making Ze300-PAN/PVDF a promising candidate for wastewater treatment applications.